Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

2. Find the inverse function [tex]f^{-1}(x)[/tex] for the given function [tex]f(x)[/tex]. Use composition to verify that the functions are inverses. Then graph the function and its inverse.

Given:
[tex]f(x)=\frac{1}{3}x-1[/tex]


Sagot :

Certainly! Let's find the inverse function [tex]\( f^{-1}(x) \)[/tex] for the given function [tex]\( f(x) = \frac{1}{3} x - 1 \)[/tex]. We will then verify that the functions are indeed inverses through composition.

### Step-by-Step Solution:

1. Express [tex]\( y \)[/tex] in Terms of [tex]\( x \)[/tex]:
Start by setting [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = \frac{1}{3} x - 1 \][/tex]

2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
To find the inverse function, swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] in the equation:
[tex]\[ x = \frac{1}{3} y - 1 \][/tex]

3. Solve for [tex]\( y \)[/tex]:
Now, we need to solve this equation for [tex]\( y \)[/tex]:
[tex]\[ x = \frac{1}{3} y - 1 \][/tex]
First, add 1 to both sides to isolate the term involving [tex]\( y \)[/tex]:
[tex]\[ x + 1 = \frac{1}{3} y \][/tex]
Next, multiply both sides by 3 to eliminate the fraction:
[tex]\[ 3(x + 1) = y \][/tex]
Simplify the expression:
[tex]\[ y = 3x + 3 \][/tex]

4. Write the Inverse Function:
Therefore, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = 3x + 3 \][/tex]

### Verification by Composition:

To verify that the functions [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex] are inverses, we need to check that [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex].

1. Check [tex]\( f(f^{-1}(x)) = x \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f(3x + 3) \][/tex]
Substitute [tex]\( 3x + 3 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(3x + 3) = \frac{1}{3} (3x + 3) - 1 \][/tex]
Simplify:
[tex]\[ f(3x + 3) = x + 1 - 1 = x \][/tex]

2. Check [tex]\( f^{-1}(f(x)) = x \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}\left( \frac{1}{3} x - 1 \right) \][/tex]
Substitute [tex]\( \frac{1}{3} x - 1 \)[/tex] into [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}\left( \frac{1}{3} x - 1 \right) = 3\left( \frac{1}{3} x - 1 \right) + 3 \][/tex]
Simplify:
[tex]\[ f^{-1}\left( \frac{1}{3} x - 1 \right) = x - 3 + 3 = x \][/tex]

Both compositions return [tex]\( x \)[/tex], confirming that the functions [tex]\( f(x) \)[/tex] and [tex]\( f^{-1}(x) \)[/tex] are indeed inverses.

### Graphing the Function and Its Inverse:

To graph the function [tex]\( f(x) \)[/tex] and its inverse [tex]\( f^{-1}(x) \)[/tex]:

- The function [tex]\( f(x) = \frac{1}{3} x - 1 \)[/tex] is a line with a slope of [tex]\( \frac{1}{3} \)[/tex] and y-intercept of -1.

- The inverse function [tex]\( f^{-1}(x) = 3x + 3 \)[/tex] is a line with a slope of 3 and y-intercept of 3.

Plotting these two lines will show that they are reflections across the line [tex]\( y = x \)[/tex]. This reflection property is a characteristic of inverse functions when graphed.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.